The Oxford history of modern war - Townshend, Charles (Oxford University Press, 2005)
How has war shaped modern society and vice versa? How has it changed over the centuries between the introduction of firearms and the invention of the atom bomb? How is war waged today? This updated edition of the classic Oxford History of Modern War brings the story into the twenty-first century, addressing the dilemma of military strategy in confronting international terrorism.